2021
DOI: 10.1002/htj.22270
|View full text |Cite
|
Sign up to set email alerts
|

MHD Williamson nanofluid across a permeable medium past an extended sheet with constant and irregular thickness

Abstract: The main resource of this paper is to establish over fluid flows sheet using mathematical modeling for constant and variable thickness by including magnetic fields, electric fields, porous medium, heat propagation/immersion, and radiative heat relocation. The Implicit Finite Difference Method (IFDM) is applied to simplify using similarity conversions to implicate partial differential equations to convert into ordinary differential equations. IFDM has been implemented in MATLAB to tabulate numerical observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Gopal et al [33] analyzed numerically nanofluid flow on a stretching sheet with the electric field, higher-order chemical reaction effects and witnessed the velocity profile increase for the electric parameter. Velocity profiles show increment behavior for progressive values of magnetic parameters for Williamson-nanofluid flow on stretching sheet was discussed by Sridhar et al [34]. Khan et al [35] analyzed Casson nanofluid flow on a rotating cylinder and detected that the temperature decrements for progressive values of Prandtl number.…”
Section: Introductionmentioning
confidence: 89%
“…Gopal et al [33] analyzed numerically nanofluid flow on a stretching sheet with the electric field, higher-order chemical reaction effects and witnessed the velocity profile increase for the electric parameter. Velocity profiles show increment behavior for progressive values of magnetic parameters for Williamson-nanofluid flow on stretching sheet was discussed by Sridhar et al [34]. Khan et al [35] analyzed Casson nanofluid flow on a rotating cylinder and detected that the temperature decrements for progressive values of Prandtl number.…”
Section: Introductionmentioning
confidence: 89%
“…Ganesh and Sridhar [31] measured the solutal and thermal transport of magnetohydrodynamic Casson fluid with radiation and moving on a permeable stretchy surface. The recently published related work is cited here [18,[36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…MHD radiative Casson-Nanofluid stream with chemical reaction through Darcy–Forchiemer medium is examined by Ganesh and Sridhar 26 . Sridhar et al 27 explore the study of MHD Williason nanofluid across a permeable medium past an extended sheet. The numerical approach of heat and mass transfer of MHD Casson fluid with chemical reaction is presented by Ganesh and Sridhar 28 – 30 , they observed that the increasing value of chemical reaction parameter is responsible of the decay in heat transfer rate.…”
Section: Introductionmentioning
confidence: 99%